Impact of Telenursing Implementation on Diet Compliance and Blood Pressure in Patients with Hypertension - Ahmad Arifin; Egi Komara Yudha; Mokh. Sandi Haryanto (Universitas Airlangga, 2024)
Introduction: Diet compliance remains a major issue in the management of hypertension. To the most recent, face to face and telenursing interventions were implemented in hypertension management. However, the impact of telenursing on diet compliance remains unknown. This study aims to determine the impact of telenursing on diet compliance and blood pressure of patients with hypertension. Methods: A quantitative quasi-experimental design with a pretest-posttest without a Control Group was applied in this study. A purposive sampling technique was applied, and 30 individuals were selected. Data were analysis with inferential statistics McNemar test and the Paired Sample T-test. Results: There was an increase in hypertension patients' dietary compliance after telenursing intervention, from 6.7% to 100%. Additionally, there was a decrease in the average systolic blood pressure from 156.8 mmHg to 145.3 mmHg and diastolic blood pressure from 105 mmHg to 94.3 mmHg. There is an influence of Telenursing on improving dietary compliance and reducing blood pressure in hypertensive patients, with respective p-value <0.001. Conclusions Telenursing demonstrated a significant positive impact on dietary compliance and blood pressure control among patients with hypertension. These findings suggest that telenursing can serve as an effective and accessible strategy to support self-management in hypertensive patients, particularly in settings with limited access to continuous face-to-face care. Despite the promising results, the absence of a control group and the relatively small sample size limit the generalizability of the findings. Further research on telenursing development and innovation was warranty.